PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATERI FLUIDA DINAMIS DI KELAS XI SEMESTER II SMA NEGERI 1 LUBUK PAKAM TAHUN AJARAN 2015/2016 - Shiddiqy, Abdul Ra’uf Ash (JURNAL IKATAN ALUMNI FISIKA, 2016)
This study aims to determine the effect of Problem Based Learning model-assisted animation to the learning outcomes of students in Dynamic Fluid material in class XI SMA Negeri 1 Lubuk Pakam Academic Year 2015/2016. This research is a quasi-experimental design with two group pretest-posttest. The population in the study were all students of class XI MIA SMA Negeri 1 Lubuk Pakam. Sampling was done by classter random sampling by taking two classes of class XI MIA as class 1 and class XI MIA Experiment 4 as grade control with each numbered 32 and 33 people. The instrument used to determine student learning outcomes are shaped achievement test essay question test with the number 12 that has been validated and the activities of assessment sheet, affective and psychomotor student. Based on the calculation of N-gain student activity result in class student activity observation experiment had significant increases student activity than the control class. And based on the results of hypothesis testing using different test (t-test) results obtained studying the application of problem based learning model using animation media has a significant increase than the learning outcomes of students who applied to conventional models in the material fluid dynamic in class XI second half of SMAN 1 Lubuk Pakam Academic Year 2015/2016.